Polyelectrolyte-Coated Mesoporous Bioactive Glasses via Layer-by-Layer Deposition for Sustained Co-Delivery of Therapeutic Ions and Drugs - Carlotta Pontremoli; Mattia Pagani; Lorenza Maddalena; Federico Carosio; Chiara Vitale-Brovarone; Sonia Fiorilli (MDPI AG, 2021)
In the field of bone regeneration, considerable attention has been addressed towards the use of mesoporous bioactive glasses (MBGs), as multifunctional therapeutic platforms for advanced medical devices. In fact, their extremely high exposed surface area and pore volume allow to load and the release of several drugs, while their framework can be enriched with specific therapeutic ions allowing to boost the tissue regeneration. However, due to the open and easily accessible mesopore structure of MBG, the release of the incorporated therapeutic molecules shows an initial burst effect leading to unsuitable release kinetics. Hence, a still open challenge in the design of drug delivery systems based on MBGs is the control of their release behavior. In this work, Layer-by-layer (LbL) deposition of polyelectrolyte multi-layers was exploited as a powerful and versatile technique for coating the surface of Cu-substituted MBG nanoparticles with innovative multifunctional drug delivery systems for co-releasing of therapeutic copper ions (exerting pro-angiogenic and anti-bacterial effects) and an anti-inflammatory drug (ibuprofen). Two different routes were investigated: in the first strategy, chitosan and alginate were assembled by forming the multi-layered surface, and, successively, ibuprofen was loaded by incipient wetness impregnation, while in the second approach, alginate was replaced by ibuprofen, introduced as polyelectrolyte layer. Zeta-potential, TGA and FT-IR spectroscopy were measured after the addition of each polyelectrolyte layer, confirming the occurrence of the stepwise deposition. In addition, the in vitro bioactivity and the ability to modulate the release of the cargo were evaluated. The polyelectrolyte coated-MBGs were proved to retain the peculiar ability to induce hydroxyapatite formation after 7 days of soaking in Simulated Body Fluid. Both copper ions and ibuprofen were co-released over time, showing a sustained release profile up to 14 days and 24 h, respectively, with a significantly lower burst release compared to the bare MBG particles.